2015
DOI: 10.1210/me.2015-1157
|View full text |Cite
|
Sign up to set email alerts
|

Minireview: Were the IGF Signaling Inhibitors All Bad?

Abstract: Preclinical studies in the 1980s defined a role for IGF signaling in the development and sustainability of the malignant process. Subsequently, antibody, tyrosine kinase, and ligand inhibitors of the IGF receptor were manufactured. In the past decade, numerous clinical trials have tested the efficacy of IGF receptor inhibitors in the treatment of advanced tumors. Early-phase trials in heavily pretreated populations showed promise with complete or partial responses in a few patients and stable disease in many m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 68 publications
0
67
0
Order By: Relevance
“…The authors further indicated that IGFIR mRNA extend to be more highly expressed in Luminal A and B subtypes compared with the basal-like and HER2-positive subtypes (173). Many IGFIR inhibitors (mAbs and TKIs) and IGF1/IGF2 neutralizing mABs have been developed and evaluated in clinical trials with some success in early trials but have failed to show benefits in larger phase III trials (174). Exploring predictive biomarkers may identify subpopulation of patients who may benefit from IGFIR inhibitors.…”
Section: 3 Other Rtksmentioning
confidence: 99%
“…The authors further indicated that IGFIR mRNA extend to be more highly expressed in Luminal A and B subtypes compared with the basal-like and HER2-positive subtypes (173). Many IGFIR inhibitors (mAbs and TKIs) and IGF1/IGF2 neutralizing mABs have been developed and evaluated in clinical trials with some success in early trials but have failed to show benefits in larger phase III trials (174). Exploring predictive biomarkers may identify subpopulation of patients who may benefit from IGFIR inhibitors.…”
Section: 3 Other Rtksmentioning
confidence: 99%
“…The IGF1R pathway is part of the insulin-related signaling network that plays a key role in development and metabolism (18). It is frequently activated in Ewing sarcoma and crucially implicated in disease progression (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Because most of these cell types are very rare (e.g. ~0.3% for MSCs, ≤0.05% for HSCs), we pooled the bone marrow from 5 mice per replicate, with 3-6 6 replicates per treatment group. We then assessed the transcriptome of each of these cell types via RNA-seq.…”
Section: Mesenchymal Stromal Cells Are the Primary Source Of Papp-a Imentioning
confidence: 99%